Characterization of anodized aluminium alloys on engineering applications - Liew, Xin Ying, 1989-; Muhamad Azizi Mat Yajid, supervisor; Fakulti Kejuruteraan Mekanikal (2013)
Project Paper (Sarjana Muda Kejuruteran (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2013